Mental health and burnout among teachers in Thailand - Paul Ratanasiripong; Nop T Ratanasiripong; Worawon Nungdanjark; Yada Thongthammarat; Shiho Toyama (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - This study investigated factors that impacted the mental health and burnout among kindergarten, primary and secondary school teachers in Thailand and presented a comprehensive intervention program to improve their wellbeing. Design/methodology/approach - This cross-sectional survey study included 267 teachers from five public schools in Thailand. The survey instruments included the Depression, Anxiety and Stress Scale and the Maslach Burnout Inventory for Educators Survey, along with data on demographics, health behaviors, finances, professional work, relationships and resilience. Findings - For teacher mental health, results indicated that family economics status, relationship quality and resilience were significant predictors of depression (R2 = 0.19); family economics status, classroom size and resilience significantly predicted anxiety (R2 = 0.13); family economics status, gender, sleep and resilience significantly predicted stress (R2 = 0.20). For teacher burnout, relationship quality and age were significant predictors of emotional exhaustion (R2 = 0.15); relationship quality and drinking significantly predicted depersonalization (R2 = 0.06); resilience and number of teaching hours significantly predicted personal accomplishment (R2 = 0.28). Originality/value - Besides providing an in-depth examination of mental health and burnout among teachers, this is the first study in Thailand to propose a comprehensive Teacher Wellness Program. This program recommends personal and professional development plans that public health personnel and school administrators could utilize to improve mental health and reduce burnout among teachers.